CCR5D32 mutation in three Brazilian populations of predominantly Sub-Saharan African ancestry - Carvalho, Mônica W.P. (2004)
This study reports the frequencies of the CCR5D32 mutation of the beta-chemokine 5 gene and discusses the possible effects of past and recent gene flow in three quilombo remnants (Brazilians communities with anthropological African ancestry whose ancestors were escaped slaves): Rio das Rãs, Mocambo, and São Gonçalo in the northeastern region of Brazil. The CCR5D32 allele frequency of the Mocambo population was significantly higher (5.6%) than that found in the Rio das Rãs (1%) and São Gonçalo (0.9%) populations. These differences may reflect different proportions of parental populations in the founders individuals, a founder-effect and/or different histories of inter-ethnic contact. The frequency of the CCR5D32 allele in the Mocambo sample is similar to that found in those urban Brazilian populations which have a large amount of European genetic input, indicating a European contribution to the gene pool of this population and suggesting that, perhaps since its foundation, Mocambo has had a high level of admixture or experienced a founder-effect.